Involvement of Nrf2-HO-1/JNK-Erk Signaling Pathways in Aconitine-Induced Developmental Toxicity, Oxidative Stress, and ROS-Mitochondrial Apoptosis in Zebrafish Embryos - Xia, Qing; Gao, Shuo; Rapael Gnanamuthu, Samuel Rajendran; Zhuang, Kaiyan; Song, Zhenzhen; Zhang, Yun; Wang, Xue; Tu, Pengfei; Li, Jianheng; Liu, Kechun (Frontiers in Pharmacology, 2021)
Aconitine (AC), one of the bioactive diterpenoid alkaloids extracted from Aconitum plants, is widely used in traditional herbal medicine to treat various diseases. Emerging evidence indicates that AC has attracted great interest for its wide cardiotoxicity and neurotoxicity. However, the toxic effects of AC on embryonic development and its underlying mechanisms remain unclear. Here, a developmental toxicity assay of AC was performed on zebrafish embryos from 4 to 96 h post fertilization (hpf), and its underlying mechanisms were discussed. AC exposure impaired the cardiac, liver, and neurodevelopment. Especially, a high dose of AC (7.27 and 8.23 μM) exposure resulted in malformations at 72 and 96 hpf, including reduced body length, curved body shape, pericardial edema, yolk retention, swim bladder and brain developmental deficiency, and degeneration of dopaminergic neurons. High-concentration AC exposure caused a deficient cardiovascular system with cardiac dysfunctions, increased heart rates at 72 and 96 hpf, and reduced locomotor behavior at 120 hpf. AC treatment significantly increased the ROS level and triggered cell apoptosis in the heart and brain regions of embryos at 96 hpf in 7.27 and 8.23 μM AC treatment zebrafish. Oxidative stress was confirmed by reduced levels of T-SOD activity associated with accumulation of lipid peroxidation in larvae. The expression levels of oxidative stress-related genes (Nrf2, HO-1, Cat, and Sod-1) Erk1/2 and Bcl-2 were significantly downregulated at 96 hpf. The expression pattern of JNK and mitochondrial apoptosis-related genes (Bad, Bax, Cyto C, Casp-9, and Casp-3) was significantly upregulated. Taken together, all these parameters collectively provide the first evidence of AC-induced developmental toxicity in zebrafish embryo/larvae through ROS-medicated mitochondrial apoptosis involving Nrf2/HO-1 and JNK/Erk pathways.